Riegos ergonómicos en el personal de enfermería que labora en Centro Quirúrgico del Hospital Provicnial Isidro Ayora - Poma Cisneros, Jenny Elizabeth (2015)
At work people develop a lot of physical and mental activity which revitalizes the body to keep it active and awake. The occupation health and safety points concerns on the implementation of measures and the development of measures necessary for the prevention of occupational hazards activities from work, The International Organization of Work IOW (2005), states that there are around 250 million of accidents annually all around the world and 3,000 people die during daily working hours, it is estimated that in Latin America and the Caribbean only around a 1% is reported and a 5% are of occupational diseases. The ergonomics originally comes from the management tool from the job, constructed with an anatomical- functional design in order to facilitate the working activities and cause absolutely no harm to the human body. The aim of this study was to identify the ergonomic hazards which are associated with biological factors to which the nursing staff are exposed to, also to define the ergonomic risks, a purpose which was developed as an observational study, descriptive and transversal, a collected survey data and direct observation was used, the universe was constructed by 25people who are currently working in the area of the Surgery Center from the Provincial Hospital Isidro Ayora. The results obtained shows that the ergonomic factors are related with the corresponding age group of young adults from 31 to 40 years of age; among the diseases that were diagnosed predominates the skeletal muscle disorder; females are mostly affected, the IMC around 60% are facing overweight problems related to risk positions, a 56% are at risk q which belongs to normal position and a 44% use risk position 2 with the possibility of damaging the musculoskeletal system. Key words: ergonomic, occupational hazards, occupational health, overweight and position.